Collection of abstracts of 20th SANCON 2019 - JSAN, Society of Anesthesiologists of Nepal (Journal of Society of Anesthesiologists of Nepal, 2019)
This submission is a collection of abstracts of 20th SANCON 2019 for JSAN.